Development of an Innovative Media Design Assessment Model in Junior High School Chemistry Learning - Hairida (Jurnal Penelitian Pendidikan IPA, 2023)
An innovative assessment model comprises a set of procedures aimed at gathering information regarding both teacher-led learning and the learning outcomes delivered through technology, such as Quizizz and Google Forms. This research aims to develop an assessment model for junior high school chemistry courses and focus on designing innovative learning materials. This research uses the R&D method with a design thinking approach, this research employed three questionnaires. The questionnaire was dedicated to assessing the validity of the assessment model framework, the validity of the assessment design, and to conduct field trials involving both educators and students. The analysis outcomes demonstrated a notably high level of validity. The assessment model framework achieved an average CVI score of 0.99, "highly validâ€ grade. Similarly, the assessment design exhibited a high level of validity, securing a score of 0.918, "highly valid" grade. Teachers and students responded favorably to this assessment model, with satisfaction levels exceeding 90%, thus confirming its validity and practicality. Consequently, this assessment model can be readily adopted by junior high school chemistry lecturers for a comprehensive assessment of student performance in chemistry classes. This is especially beneficial in the context of creating innovative learning materials, ultimately enhancing the effectiveness of chemistry education in junior high schools and aligning it with the demands of the 21st century.